2019
DOI: 10.1101/684951
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alpha/Beta Hydrolase Domain-Containing Protein 2 regulates the rhythm of follicular maturation and estrous stages of the female reproductive cycle

Abstract: Therian female fertility is defined by a successful and strictly periodic ovarian cycle, which is under the control of gonadotropins and steroid hormones, particularly progesterone and estrogen. The latter two are produced by the ovaries that are engaged in controlled follicular growth, maturation and release of the eggs, i.e. ovulation. It is well known that steroid hormones regulate ovarian cycles via genomic signaling, by altering gene transcription and protein synthesis. However, despite this well-studied … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…ABHD2 has been shown to regulate ion channel activation in human sperm cells by breaking down the endocannabinoid 2-arachidonoylglycerol in the cell membrane ( Miller et al, 2016 ). However, CPECs isolated from global Abhd2 knockout mice that were generated in our laboratory ( Björkgren et al, 2019 Preprint ) showed activation of Kir7.1 similar to that of cells from wild-type animals ( Fig. 4, E and F ), thus negating any possible effect of the receptor on Kir7.1 activation.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…ABHD2 has been shown to regulate ion channel activation in human sperm cells by breaking down the endocannabinoid 2-arachidonoylglycerol in the cell membrane ( Miller et al, 2016 ). However, CPECs isolated from global Abhd2 knockout mice that were generated in our laboratory ( Björkgren et al, 2019 Preprint ) showed activation of Kir7.1 similar to that of cells from wild-type animals ( Fig. 4, E and F ), thus negating any possible effect of the receptor on Kir7.1 activation.…”
Section: Resultsmentioning
confidence: 92%
“…All experiments were performed in accordance with National Institutes of Health guidelines for animal research and approved by the University of California, Berkeley Animal Care and Use Committee (AUP 2015–07-7742), with every effort made to minimize suffering for the animals. A thorough description of how the Abhd2 full knockout mouse line was generated is provided elsewhere ( Björkgren et al, 2019 Preprint ).…”
Section: Methodsmentioning
confidence: 99%
“…Abhd2 has been previously characterized as a monoacylglycerol lipase with potent effects on male fertility[24] and ovulation in female mice [23]. In sperm, Abhd2 is activated by progesterone, cleaves monoacylglycerols (1-arachadonoylglycerol and 2-arachadonoylglycerol) to remove the inhibition of the CatSper calcium channel thereby allowing for sperm activation.…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone-induced activation of Abhd2 is required for its lipid cleavage function and regulating ovulation in females [23,24]; however, the effect of male sex hormones on Abhd2 has not been demonstrated. In a study of cerebral cortex development, a perinatal testosterone spike in male mice drove mitochondrial lipid composition and maturation [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation